KESEJAHTERAAN KESEHATAN ANAK PADA MASA PANDEMI COVID-19 DI PANTI ASUHAN AMANAH ASSOMADIYAH - Intan Diana Fauziyah; Wahyuni Retnowulandari (Fakultas Hukum Universitas Trisakti, 2022)
The purpose of this research is to provide the health of foster children at the Amanah Assomadiyah orphanage during the Covid-19 pandemic and for Children at an age that is prone to being infected with Covid-19. The health of Indonesian children is something that must not be forgotten during this pandemic. Indonesian children's health is something that must be considered and maintained. The legal task is to ensure the welfare of children according to Law Number 4 of 1979 concerning Children’s Welfare. This research’s main problems: what are the fulfillment of the health of foster children at the Amanah Assomadiyah Orphanage during the Covid-19 pandemic and what are the efforts to fulfill the health of children during the Covid-19 pandemic at the Amanah Assomadiyah Orphanage that based on statutory regulations. The research conducted in normative and descriptive analytical legal research and the conclusions are drawn using deductive logic method. The conclusions of this research are that the fulfillment of children's health at the Amanah Assomadiyah orphanage was disrupted during the Covid-19 pandemic and The administrators of the Amanah Assomadiyah orphanage are basically unable to provide health service efforts and children's health needs.